Further Evidence That MicroRNAs Can Play a Role in Hemophilia A Disease Manifestation: F8 Gene Downregulation by miR-19b-3p and miR-186-5p - Jankowska, Katarzyna I.; McGill, Joseph; Pezeshkpoor, Behnaz; Oldenburg, Johannes; Sauna, Zuben E.; Atreya, Chintamani D. (Frontiers in Cell and Developmental Biology, 2020)
Hemophilia A (HA) is a F8 gene mutational disorder resulting in dysfunctional FVIII protein. However, surprisingly in few cases, HA is manifested even without mutations in F8. To understand this anomaly, we recently sequenced microRNAs (miRNAs) of two patients with mild and moderate HA with no F8 gene mutations and selected two highly expressing miRNAs, miR-374b-5p and miR-30c-5p from the pool to explain the FVIII deficiency that could be mediated by miRNA-based F8/FVIII suppression. In this report, an established orthogonal in vivo RNA-affinity purification approach was utilized further to directly identify a group of F8-interacting miRNAs and tested them for F8/FVIII suppression. From this pool, two microRNAs, miR-19b-3p and miR-186-5p found to be upregulated in a severe HA patient with a mutation in the F8 coding sequence and two HA patients without mutations in the F8 coding sequence were selected to demonstrate their role in F8 gene expression regulation in mammalian cells. Overall, these results provide further evidence for the hypothesis that by targeting the 3’UTR of F8, miRNAs can modulate FVIII protein levels. This mechanism could either be the primary cause of HA in patients who lack F8-mutaions or, control the severity of the disease in patients with F8 mutations.